An ultralow base weight of nanocellulose boosting filtration performance of hierarchical composite air filter inspired by native spider web. (1st December 2021) - Xiong, Zhenjun; Li, Xiuhong; Wang, Jie; Bian, Fenggang; Lin, Jinyou
Abstract: The beauty of nature is inexhaustible to human beings, and the process of human understanding and learning nature promotes the progress of science and technology. Inspired by the natural hierarchical spider-web structure, a biomimetic composite air filter with high filtration performance and good wet stability is prepared for the first time. Cellulose nanofibrils (CNF) generated from regenerable jute plants are implanted into the pores of commercialized biodegradable porous corrugated papers and self-assembled into robust nano-networks as filter building blocks to prepare a biodegradable composite air filter. When the base weight of CNF goes up to only 0.2500 g/m 2, the CNF nano-networks completely fill the pores of corrugated paper, which greatly reduces the consumption of raw materials. More importantly, the filtration efficiency for PM0.3 removal of resultant corrugated paper is increased from 6% to 94.5%, while maintaining a relatively low pressure drop of 296.3 Pa. After a silane modification of CNF, the filtration efficiency of 75% can be achieved at high humidity. Overall, the successful synthesis of biomimetic composite air filters provides inspiration for the design of separation materials, satisfying the growing demand for renewability, sustainability, and biodegradability. Highlights: A biomimetic composite air filter with ultralow base weight has been developed. Cellulose nanofibrils were self-assembled into robust nano-networks. A high efficiency of 94.5% and low pressure drop of 296.3 Pa were achieved. A filtration efficiency of 75% for PM0.3 could be achieved at 80% RH. All the materials we used are biodegradable.